2014
DOI: 10.1007/s40262-013-0111-4
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of CYP3A and ABCB1 Phenotyping Probes for the Pharmacokinetics of Sunitinib: the ClearSun Study

Abstract: Phenotype tests for ABCB1 and CYP3A4 did not explain inter-individual variability of sunitinib exposure sufficiently. However, the correlation between sunitinib clearance and the occurrence of severe toxicity suggests a direct exposure-toxicity relationship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…No statistically significant differences were observed in the PK parameter estimates of sorafenib ( Figure d ). Although the mean ratio between 1’‐hydroxymidazolam and midazolam, used as a measure of CYP3A4 activity changes, was ∼2 times higher after rifampin intake ( P = 0.005; Figure e ), the extent of sorafenib‐N‐oxide formation was not different between treatment cycles ( Figure f ). During the course of the clinical study, no toxicities were observed that could be attributed to rifampin or midazolam.…”
Section: Resultsmentioning
confidence: 99%
“…No statistically significant differences were observed in the PK parameter estimates of sorafenib ( Figure d ). Although the mean ratio between 1’‐hydroxymidazolam and midazolam, used as a measure of CYP3A4 activity changes, was ∼2 times higher after rifampin intake ( P = 0.005; Figure e ), the extent of sorafenib‐N‐oxide formation was not different between treatment cycles ( Figure f ). During the course of the clinical study, no toxicities were observed that could be attributed to rifampin or midazolam.…”
Section: Resultsmentioning
confidence: 99%
“…For sunitinib, several population PK models have been developed . The PK of sunitinib and SU012662 is described as a one‐ or two‐compartment model with first‐order absorption and elimination.…”
Section: Methodsmentioning
confidence: 99%
“…For sunitinib, several population PK models have been developed. 96,[113][114][115][116][117][118][119][120] The PK of sunitinib and SU012662 is described as a one-or two-compartment model with first-order absorption and elimination. Some covariates might explain part of the interpatient PK variability.…”
Section: Factors Identified In Pharmacokinetic Models That Explain Inmentioning
confidence: 99%
“…Three PK models for sunitinib and SU12662 have been described thus far . Houk's model, albeit based on a rich dataset (590 subjects), disregarded irrationally the correlation between the parent and metabolite compounds which share similar PK pathways .…”
Section: Introductionmentioning
confidence: 99%